Peningkatan Kompetensi Pengelola Perpustakaan Sekolah Melalui Bimtek di Kabupaten Solok Selatan - Erida; Gusnar Zain; Sefri Doni; Rahmi Yunita; Sisi Susanti (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This study aims to formulate technical guidance to improve the competence of school library managers in South Solok Regency. This research emphasizes the ability of library management in accordance with the National Library Standards so that after the technical guidance of library managers in South Solok Regency especially Pauh Duo District can innovate and competence increases. This technical guidance model was developed with research and development. The results showed that the technical guidance model needs to be TESTED to improve the competency of managing national standard libraries.